Parallel Parkin: Cdc20 Takes a New Partner - Meza-Gutierrez, Fernando (Mol Cell, 2015)
CDC20 and CDH1 are well-established substrate receptors for the Anaphase Promoting Complex/Cyclo-some (APC/C). In this issue of Molecular Cell, Lee et al. (2015) show that these adaptors can also target cell cycle proteins for destruction through a second ubiquitin ligase, Parkin.